2020
DOI: 10.1038/s41419-020-03186-2
|View full text |Cite
|
Sign up to set email alerts
|

YTHDC1 mitigates ischemic stroke by promoting Akt phosphorylation through destabilizing PTEN mRNA

Abstract: YTH Domain Containing 1 (YTHDC1) is one of the m6A readers that is essential for oocyte development and tumor progression. The role of YTHDC1 in neuronal survival and ischemic stroke is unknown. Here, we found that YTHDC1 was unregulated in the early phase of ischemic stroke. Knockdown of YTHDC1 exacerbated ischemic brain injury and overexpression of YTHDC1 protected rats against brain injury. Mechanistically, YTHDC1 promoted PTEN mRNA degradation to increase Akt phosphorylation, thus facilitating neuronal sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 42 publications
0
73
0
Order By: Relevance
“…Absorbance data were obtained using a 96-well plate reader (Molecular Devices, USA) at 490 nm. LDH release (%) was calculated by calculating the ratio of experimental LDH release to control LDH release according to the manufacturer’s instructions [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Absorbance data were obtained using a 96-well plate reader (Molecular Devices, USA) at 490 nm. LDH release (%) was calculated by calculating the ratio of experimental LDH release to control LDH release according to the manufacturer’s instructions [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…A role for m 6 A readers as regulators of the brain response to stroke has also been proposed. YTHDC1 levels increased following ischemia in rats while YTHDF1, 2, and 3 levels were repressed ( Zhang et al, 2020 ). Elevated YTHDC1 levels may support post-ischemic neuronal survival via the modulation of the Akt/PTEN pathway ( Zhang et al, 2020 ).…”
Section: A In Brain Disordersmentioning
confidence: 99%
“…YTHDC1 levels increased following ischemia in rats while YTHDF1, 2, and 3 levels were repressed ( Zhang et al, 2020 ). Elevated YTHDC1 levels may support post-ischemic neuronal survival via the modulation of the Akt/PTEN pathway ( Zhang et al, 2020 ). YTHDF1 reduction may be a protective or adaptive mechanism by limiting post-stroke inflammation ( Zheng et al, 2020 ).…”
Section: A In Brain Disordersmentioning
confidence: 99%
“…Thus hypothermia could activate PI3K/Akt signaling to protect neurons from I/R-induced pyroptosis ( Diao et al, 2020 ). Another study reported that the m 6 A reader YTHDC1 protects ischemic stroke through mediating PTEN mRNA degradation, which further promotes Akt phosphorylation and facilitates neuronal survival ( Zhang Z. et al, 2020 ). These two studies demonstrate that m 6 A modification could modulate PTEN expression to regulate PI3K/Akt signaling in I/R injury.…”
Section: A In Neurological Disorders and Injuriesmentioning
confidence: 99%